Insulin prescribing pattern in geriatric type 2 diabetic mellitus patients of different nutritional status at a tertiary level of health care: a retrospective study - Dias, Deidre L.; Gomes, Edwin J. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The world, specifically India is witnessing a steady increase in elderly population. The numbers are expected to escalate by 3 million by 2050 considering India alone. Further, the diabetic population is also increasing, and India will be home to the highest population of diabetic patients. It is thus indispensable to understand the prescribing patterns in elderly diabetics where insulin is inevitably added later in the course of diabetes, if not earlier. Methods: Data was extracted from a diabetic registry maintained of patients attending the outpatient departments of a tertiary health care between 2009 to 2012 and having completed one year of regular three-monthly follow ups. Data was entered into MS Excel, analysed using IBM SPSS software and presented in the form of percentages or averages. Results: Out of the total 180 male predominated type 2 diabetics aged 60 years and above, 142 (78.8%) elderly patients received a single type of insulin each day. 102 (56.6%) patients were on human insulins while 82 (45.5%) were receiving analogues. As for premixed insulins, 62 (34.4%) patients were receiving biphasic insulin analogues, while 83 (46.1%) patients were receiving human premixed insulin. Conclusions: The elderly population makes up for a huge proportion and is set to increase in the coming years. The insulin prescribing pattern in them needs to be tailor-made to suit their needs and preferences whilst maintaining a relaxed target of HbA1c control at 8mg% or less. However, it should not be too low so as to avoid unnecessary hypoglycaemic episodes.